Whole Arm Water Displacement Volumetry Is a Reliable and Sensitive Measure: A Pilot to Assess Acute Postburn Volume Change. Issue 6 (November 2016) - Edgar, Dale W.; Briffa, N. Kathy; Wood, Fiona M.
Abstract : Water displacement volumetry (WDV) is a reliable method for measurement of wrist and hand volume in lymphedema patients. However, within session WDV reliability for the whole upper limb (UL) lacks comprehensive investigation, particularly in acute edema populations. This study aimed to confirm the reliability and investigate the impact of time between repeated trials on the sensitivity of WDV as a measure of whole UL volume change in an uninjured cohort and a burn injured pilot group. Within session, duplicate measures of whole UL WDV were recorded in two groups of noninjured volunteers and a group of burn patients. Each noninjured group differed only in the time between WDV repeats. The reliability trials were performed <10 minutes apart (T10 ) and 20 to 30 minutes apart (T20 ). The time between repetitions for burn patients was 20 to 30 minutes, based on the results of the noninjured participant trials. All trial groups demonstrated excellent correlation between trials (ICCT10 = 0.999, ICCT20 = 0.997). The minimum detectable difference calculated for WDV when measuring whole UL volume change of >50 ml for noninjured and >100 ml for burn patients. Despite this, a systematic bias was demonstrated between the T10 group means. The T20 group trials did not indicate such error on statistical testing ( P = .297). The study confirms that WDV measurement of whole ULs is reliable and sensitive, if used at least 20 minutes apart. However, a significant and clinically relevant subject-by-method interaction was demonstrated. Researchers and clinicians are reminded to be aware of the performance of the technique when designing investigations in patient populations.